2016
DOI: 10.1016/j.bpj.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Complexin Accessory Helix with Synaptobrevin Regulates Spontaneous Fusion

Abstract: Neuronal transmitters are released from nerve terminals via the fusion of synaptic vesicles with the plasma membrane. Vesicles attach to membranes via a specialized protein machinery composed of membrane-attached (t-SNARE) and vesicle-attached (v-SNARE) proteins that zipper together to form a coiled-coil SNARE bundle that brings the two fusing membranes into close proximity. Neurotransmitter release may occur either in response to an action potential or through spontaneous fusion. A cytosolic protein, Complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 55 publications
2
30
2
Order By: Relevance
“…This can be clearly illustrated by recordings of mEJCs from complexin null mutant ( Figure 6A). Spontaneous activity is drastically elevated in this mutant 32 , and therefore mEJPs recorded intracellularly overlap and cannot be clearly distinguished from each other (Figure 6B), while focal recordings 22 enable accurate detection of spontaneous release events ( Figure 4A).…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be clearly illustrated by recordings of mEJCs from complexin null mutant ( Figure 6A). Spontaneous activity is drastically elevated in this mutant 32 , and therefore mEJPs recorded intracellularly overlap and cannot be clearly distinguished from each other (Figure 6B), while focal recordings 22 enable accurate detection of spontaneous release events ( Figure 4A).…”
Section: Representative Resultsmentioning
confidence: 99%
“…In contrast, the activity of a limited number of the sites of release can be recorded focally by positioning a micropipette tip near neuronal terminals or synaptic varicosities. This technique was originally employed by Katz and Miledi 2 , and focal extracellular recordings have been successfully employed at several NMJ preparations, including frog 3,4,5 , mouse 6,7,8 , crustacean 9,10,11,12,13,14,15,16 , and Drosophila 17,18,19,20,21,22,23 . This approach was further developed by Dudel, who optimized macropatch recoding electrodes 24,25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach enabled reliable recordings of EJCs and mEJCs using fire polished electrodes of a tip diameter ranging from 1–3 to 10 µm, and it closely matches the loose‐patch‐clamp method . Focal macropatch recordings have been successfully employed at several NMJ preparations, including frog, mouse, crustacean, and Drosophila . Simultaneous recordings by two or three mactopatch electrodes from the same NMJ, as well as moving the electrode along the NMJ, demonstrated that a macropatch electrode predominantly records the activity of synaptic boutons under the electrode tip, although the boutons positioned under the electrode rim and those in the immediate proximity to the electrode tip can make a minor contribution to the recorded EJCs.…”
Section: Focal Extracellular Recordingsmentioning
confidence: 89%
“…These advantages enable recordings of EJCs and mEJCs from a selected bouton (Figure (a) and (b)). Respectively, this technique is advantageous for quantitative studies of release kinetics in the mutants with enhanced spontaneous activity and altered release time‐course (Figure (c)), such the complexin null mutant . The rapid mEJC time‐course and limited number of release sites enable accurate detection of neurosecretory quanta, which can be performed automatically (Figure (d)) .…”
Section: Focal Extracellular Recordingsmentioning
confidence: 99%